(untitled) (Research, Society and Development, 2020)
This research aims to present the importance of the pharmaceutical professional’s performance in face of the COVID-19 pandemic. It is a bibliographic review that was conducted based on data collected from the Science Direct, Pubmed, Medline and official Brazilian government websites. As inclusion criteria, articles from 2019 and 2020 were selected from September 15, 2019 to May 13, 2020, in English and complete dealing with the theme in question. The results found indicate that the performance of the pharmacist in the health teams that are facing this pandemic is fundamental since this professional has the knowledge of the drugs, their interactions and adverse reactions to drugs. The management of the hospital pharmacy at this time is essential so that there is no shortage of medication or waste, and within community pharmacies the pharmacist’s performance is through information on prevention and control of COVID-19, as well as guidance for those patients who already have other comorbidities and make continuous use of medication. Thus, the community and clinical pharmacist who is acting in the face of this pandemic has become an indispensable professional since he has full support to integrate the health teams to contribute with his knowledge and skill about the drugs.